2022
DOI: 10.22541/au.165375542.20422124/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiovascular Complications of Modern Multiple Myeloma Therapy: A Pharmacovigilance Study

Abstract: Background: Multiple myeloma accounts for over 15% of hematological malignancies. In attempt to tackle this malady, the FDA approved four drugs in 2015 which has propagated further development of new anti-multiple myeloma since. However, the health safety of these new agents is still ill-defined. The aim of this study is to delineate the cardiovascular adverse events of these drugs. Methods: We searched the cardiac adverse events of the newly approved FDA drugs since 2015 using the U.S. Food and Drug Administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…An important limitation of the study refers to the exclusion of patients with CV symptoms (hypertension, HF, unstable angina or ischemic heart disease) in the 6 months preceding the trial (103). A pharmacovigilance study comparing ixazomib with other approved drugs for MM reported an increased risk of atrial fibrillation (HR: 1.9, 95% CI: 1.5-2.3) among ixazomib users (104).…”
Section: Ixazomibmentioning
confidence: 99%
“…An important limitation of the study refers to the exclusion of patients with CV symptoms (hypertension, HF, unstable angina or ischemic heart disease) in the 6 months preceding the trial (103). A pharmacovigilance study comparing ixazomib with other approved drugs for MM reported an increased risk of atrial fibrillation (HR: 1.9, 95% CI: 1.5-2.3) among ixazomib users (104).…”
Section: Ixazomibmentioning
confidence: 99%